Object-Role Modeling: Principles and Benefits - Halpin, Terry (ACM Digital Library, 2010)
Object-Role Modeling (ORM) is an approach for modeling and querying information at the conceptual level, and for transforming ORM models and queries to or from other representations. Unlike attribute-based approaches such as Entity-Relationship (ER) modeling and class modeling within the Unified Modeling Language (UML), ORM is fact-oriented, where all facts and rules are modeled in terms of natural sentences easily understood and validated by nontechnical business users. ORM’s modeling procedure facilitates validation by verbalization and population with concrete examples. ORM’s graphical notation is far more expressive than that of ER diagrams or UML class diagrams, and its attribute-free nature makes it more stable and adaptable to changing business requirements. This article explains the fundamentals of ORM, illustrates some of its advantages as a data modeling approach, and outlines some recent research to extend ORM, with special attention to mappings to deductive database